Preparation method of temperature-resistant polymer modified semi-solid lithium battery diaphragm
By coating ceramic particle material on the semi-solid lithium battery separator, spraying acrylic acid and performing ultraviolet grafting, the durability of the separator in a high-temperature liquid environment is solved, and the safety performance and service life of the battery are improved.
Patent Information
- Application Number
- CN202411929507.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-25
AI Technical Summary
The separator of semi-solid lithium batteries is not durable in high-temperature liquid environments, resulting in reduced battery performance and increased safety risks.
The combination of polyethylene diaphragm, ceramic particle material and acrylic acid is used to improve the mechanical properties and chemical stability of the diaphragm through the coating of ceramic particle material, acrylic spraying and ultraviolet grafting technology.
It improves the heat resistance, breathability and wettability of the diaphragm, and enhances the safety performance and service life of the battery.
Smart Images

Figure HDA0005209929480000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery separators, and in particular to a method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator. Background Art
[0002] In the structure of semi-solid lithium batteries, the diaphragm is one of the key internal components. The performance of the diaphragm determines the interface structure, internal resistance, etc. of the semi-solid lithium battery, and directly affects the capacity, cycle and safety performance of the semi-solid lithium battery. A diaphragm with excellent performance plays an important role in improving the comprehensive performance of semi-solid lithium batteries.
[0003] The Chinese patent with the announcement number CN103943804B discloses a heat-resistant and safe lithium-ion battery separator, comprising a base layer and a ceramic coating on the base layer; the raw materials of the base layer include: nano-dispersant, inorganic nano-particles, antioxidant, PTFE dispersion, polyethylene powder and paraffin oil, wherein the antioxidant is used in an amount of 0.1-0.5% of the polyethylene powder; the inorganic nano-particles are used in an amount of 1-6% of the polyethylene powder; the PTFE dispersion is used in an amount of 0-30% of the polyethylene powder; the polyethylene powder is used in an amount of 5-40% of the paraffin oil; the mass ratio of the nano-dispersant to the inorganic nano-particles is (1:20)-(1:90); the solid content of the PTFE dispersion is 50-60%. This patent effectively solves the problems of ceramic coating shedding, heat resistance and safety problems of lithium-ion batteries caused by the separator.
[0004] In actual use, the battery separator of the above patent has a certain amount of liquid electrolyte in the semi-solid lithium battery, which causes mutual influence between the battery separator and the high-temperature liquid, which is not conducive to long-term use; therefore, it does not meet the existing needs. In this regard, we propose a method for preparing a heat-resistant polymer semi-solid lithium battery separator. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator, which solves the problem that during the actual use of the battery separator proposed in the above background technology, the semi-solid lithium battery has a certain amount of liquid electrolyte, which leads to mutual influence between the battery separator and the high-temperature liquid, which is not conducive to long-term use.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for preparing a heat-resistant polymer-transferred semi-solid lithium battery separator, wherein the heat-resistant polymer-transferred semi-solid lithium battery separator is composed of a polyethylene separator, a ceramic particle material and acrylic acid, and the preparation method comprises the following steps:
[0007] S1: Preparation of polyethylene diaphragm;
[0008] S2: Select ceramic particle material and coat it on the surface of polyethylene diaphragm;
[0009] S3: spray acrylic acid on the surface of the diaphragm to make it evenly adhere to the surface of the diaphragm;
[0010] S4: UV light is used to perform UV grafting on acrylic acid and the diaphragm to shape the surface material of the diaphragm.
[0011] Preferably, in S1, the method for preparing the polyethylene diaphragm comprises the following steps:
[0012] S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet;
[0013] S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil;
[0014] S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller;
[0015] S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
[0016] Preferably, the method for preparing the ceramic particle material comprises the following steps:
[0017] S2-1: Adding nano-alumina powder to special ceramic raw materials, and mixing them;
[0018] S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container;
[0019] S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas, and the metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod, finally obtaining ceramic nanoparticles;
[0020] S2-4: Introduce the ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed.
[0021] Preferably, the acrylic acid in S3 is prepared by the following steps:
[0022] S3-1: After the hydrolysis temperature is set to 90-100°C, sulfuric acid with a concentration of 55%-85% is added to acrylonitrile, and acrylonitrile is completely converted after 1 hour;
[0023] S3-2: The converted acrylonitrile is hydrolyzed for a second time by adding water, and the reaction temperature is increased to 125-135° C.;
[0024] S3-3: The hydrolyzate obtained after heating is decompressed, stabilized, and then distilled to obtain acrylic acid.
[0025] Preferably, the ultraviolet light grafting in S4 comprises the following steps:
[0026] S4-1: After spraying acrylic acid on the cleaned surface of the diaphragm, dry it;
[0027] S4-2: dissolving the photoinitiator in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L;
[0028] S4-3: Soak the initiator solution on the surface of the diaphragm in the dark for 30 minutes;
[0029] S4-4: Methanol and ethanol are prepared into monomer solutions of different concentrations, the membrane adsorbed with the photoinitiator is placed in the monomer solution and filled with nitrogen for protection, the single-necked flask is placed in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, the membrane is continuously transported, and continuous irradiation grafting is performed;
[0030] S4-5: After the irradiation is completed, the product is cleaned with distilled water, and after the cleaning is completed, vacuum drying is performed.
[0031] Preferably, in S1-1, the polyethylene material is one of high-density polyethylene, low-pressure polyethylene, ultra-high molecular weight polyethylene, modified polyethylene, and cross-linked polyethylene.
[0032] Preferably, in S1-2, the extractant is a neutral oxygen-containing extractant selected from alcohol ethers, ketones and ester compounds.
[0033] Preferably, the raw material of the nano-alumina powder of S2-1 is obtained by dehydrating aluminum hydroxide at a low temperature of 140-150°C to obtain type A alumina.
[0034] Preferably, in S2-3, the low-pressure inert gas is one of helium, neon, argon, krypton and xenon with a gas pressure of 2 KPa.
[0035] Preferably, in S3-1, acrylonitrile is obtained by reacting acetylene and hydrocyanic acid at 80-90° C. under the catalysis of a dilute hydrochloric acid solution of cuprous chloride-potassium chloride-sodium chloride.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The present invention selects ceramic particle materials to be coated on the surface of the polyethylene diaphragm. The ceramic particle materials have excellent mechanical properties, wear resistance and chemical stability. Polymer materials are used to improve the inherent defects of the materials, give the materials new functions, and reduce the cost of using the materials. Ultraviolet light is used to graft acrylic acid and the diaphragm to shape the surface materials of the diaphragm, and the surface grafting modification of the battery diaphragm is performed. As the grafting rate increases, the hydrophilicity of the diaphragm is improved, the air permeability is increased, and the porosity and air permeability are reduced. The method of ultraviolet light irradiation inducing surface grafting of polar monomers is used to improve the surface properties of the battery diaphragm and increase its wettability to the electrolyte.
[0038] 2. The present invention adds nano-alumina to ceramic particles. The nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of the material, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance. Ceramic nanoparticles have a large specific surface area and size effect, which can enhance the mechanical properties, thermal conductivity and optical properties of the diaphragm surface, and can also improve the processing performance and density of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In order to solve the problem that the existing battery separators have a certain amount of liquid electrolyte in the actual use process, which leads to the mutual influence between the battery separator and the high-temperature liquid, which is not conducive to long-term use, please refer to Figure 1 , this embodiment provides the following technical solutions:
[0042] Example 1
[0043] A method for preparing a heat-resistant polymer-transferred semi-solid lithium battery separator, wherein the heat-resistant polymer-transferred semi-solid lithium battery separator is composed of a polyethylene separator, a ceramic particle material and acrylic acid, and the preparation method comprises the following steps:
[0044] S1: Preparation of polyethylene diaphragm;
[0045] S2: Ceramic particle materials are selected to be coated on the surface of the polyethylene diaphragm. Ceramic particle materials have excellent mechanical properties, wear resistance and chemical stability. Polymer materials are used to improve the inherent defects of materials, give materials new functions and reduce the cost of material use;
[0046] S3: spray acrylic acid on the surface of the diaphragm to make it evenly adhere to the surface of the diaphragm;
[0047] S4: Use ultraviolet light irradiation to perform ultraviolet light grafting on acrylic acid and diaphragm to shape the surface material of the diaphragm and perform surface grafting modification on the battery diaphragm. As the grafting rate increases, the hydrophilicity of the diaphragm increases, the air permeability increases, and the porosity and air permeability decrease.
[0048] In this embodiment, in S1, the method for preparing the polyethylene diaphragm comprises the following steps:
[0049] S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet;
[0050] S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil;
[0051] S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller;
[0052] S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
[0053] In this embodiment, the method for preparing the ceramic particle material comprises the following steps:
[0054] S2-1: Add nano-alumina powder to special ceramic raw materials, and mix them separately. Nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials;
[0055] S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container;
[0056] S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas. The metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod to finally obtain ceramic nanoparticles. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of materials, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance;
[0057] S2-4: Introduce ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed. Ceramic nanoparticles have a large specific surface area and size effect, which can enhance the mechanical properties, thermal conductivity, and optical properties of the diaphragm surface, and can also improve the processing performance and density of the material.
[0058] In this embodiment, the acrylic acid in S3 is prepared by the following steps:
[0059] S3-1: After the hydrolysis temperature is set to 90°C, 55% sulfuric acid is added to acrylonitrile, and acrylonitrile is completely converted after 1 hour;
[0060] S3-2: The converted acrylonitrile is hydrolyzed for a second time by adding water, and the reaction temperature is increased to 125°C;
[0061] S3-3: The hydrolyzate obtained after heating is decompressed, stabilized, and then distilled to obtain acrylic acid.
[0062] In this embodiment, the ultraviolet light grafting in S4 includes the following steps:
[0063] S4-1: After spraying acrylic acid on the cleaned surface of the diaphragm, dry it;
[0064] S4-2: dissolving the photoinitiator in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L;
[0065] S4-3: Soak the initiator solution on the surface of the diaphragm in the dark for 30 minutes;
[0066] S4-4: Methanol and ethanol are prepared into monomer solutions of different concentrations, the diaphragm adsorbed with the photoinitiator is placed in the monomer solution and filled with nitrogen for protection, the single-necked flask is placed in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, the diaphragm is continuously transported, and continuous irradiation grafting is performed. The surface properties of the battery diaphragm are improved by ultraviolet irradiation to induce surface grafting of polar monomers and increase its wettability to the electrolyte;
[0067] S4-5: After the irradiation is completed, the product is cleaned with distilled water, and after the cleaning is completed, vacuum drying is performed.
[0068] In this embodiment, in S1-1, the polyethylene material adopts one of high-density polyethylene, low-pressure polyethylene, ultra-high molecular weight polyethylene, modified polyethylene, and cross-linked polyethylene, and has excellent low-temperature resistance, good chemical stability, resistance to corrosion by most acids and alkalis, low water absorption, and excellent electrical insulation properties.
[0069] In this embodiment, in S1-2, the extractant is a neutral oxygen-containing extractant selected from alcohol ethers, ketones and ester compounds. The main reason why such extractants can extract metals is that they can form complexes with metals and enter the organic phase to be extracted.
[0070] In this embodiment, the raw material of the nano-alumina powder S2-1 is type A alumina obtained by dehydrating aluminum hydroxide at a low temperature of 140-150°C. Type A alumina has excellent resistance to anodic oxygen erosion. When used in organic coatings, it can significantly improve the oxidation resistance of the coatings, and can transfer stress in an environment where the coatings are subjected to alternating hot and cold temperatures, thereby reducing the generation of cracks.
[0071] In this embodiment, in S2-3, the low-pressure inert gas is one of helium, neon, argon, krypton and xenon with a gas pressure of 2 KPa, so that the ultrafine particles evaporate and then quickly condense to form nano powder.
[0072] In this embodiment, in S3-1, acrylonitrile is obtained by reacting acetylene and hydrocyanic acid at 80-90°C under the catalytic action of a dilute hydrochloric acid solution of cuprous chloride-potassium chloride-sodium chloride. Acrylonitrile is an important monomer for synthetic fibers, synthetic rubbers and synthetic resins. The rubber body obtained by copolymerizing acrylonitrile with a polyethylene diaphragm has good oil resistance, cold resistance, wear resistance, and electrical insulation properties, and is relatively stable under the action of most chemical solvents, sunlight and heat to improve the temperature resistance effect.
[0073] Example 2
[0074] A method for preparing a heat-resistant polymer semi-solid lithium battery separator comprises the following steps:
[0075] S1: Preparation of polyethylene diaphragm;
[0076] S2: Ceramic particle materials are selected to be coated on the surface of the polyethylene diaphragm. Ceramic particle materials have excellent mechanical properties, wear resistance and chemical stability. Polymer materials are used to improve the inherent defects of materials, give materials new functions and reduce the cost of material use;
[0077] S3: spray acrylic acid on the surface of the diaphragm to make it evenly adhere to the surface of the diaphragm;
[0078] S4: Use ultraviolet light irradiation to perform ultraviolet light grafting on acrylic acid and the separator to shape the surface material of the separator and perform surface grafting modification on the battery separator. As the grafting rate increases, the hydrophilicity of the separator increases, the air permeability increases, and the porosity and air permeability decrease;
[0079] S5: After drying, the separator is attached to the semi-solid lithium battery.
[0080] In this embodiment, in S1, the method for preparing the polyethylene diaphragm comprises the following steps:
[0081] S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet;
[0082] S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil;
[0083] S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller;
[0084] S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
[0085] In this embodiment, the method for preparing the ceramic particle material comprises the following steps:
[0086] S2-1: Add nano-alumina powder to special ceramic raw materials, and mix them separately. Nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials;
[0087] S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container;
[0088] S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas. The metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod to finally obtain ceramic nanoparticles. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of materials, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance;
[0089] S2-4: Introduce ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed. Ceramic nanoparticles have a large specific surface area and size effect, which can enhance the mechanical properties, thermal conductivity, and optical properties of the diaphragm surface, and can also improve the processing performance and density of the material.
[0090] In this embodiment, the acrylic acid in S3 is prepared by the following steps:
[0091] S3-1: After the hydrolysis temperature is set to 95°C, sulfuric acid with a concentration of 70% is added to acrylonitrile, and acrylonitrile is completely converted after 1 hour;
[0092] S3-2: The converted acrylonitrile is hydrolyzed for a second time by adding water, and the reaction temperature is increased to 125-135° C.;
[0093] S3-3: The hydrolyzate obtained after heating is decompressed, stabilized, and then distilled to obtain acrylic acid.
[0094] In this embodiment, the ultraviolet light grafting in S4 includes the following steps:
[0095] S4-1: After spraying acrylic acid on the cleaned surface of the diaphragm, dry it;
[0096] S4-2: dissolving the photoinitiator in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L;
[0097] S4-3: Soak the initiator solution on the surface of the diaphragm in the dark for 30 minutes;
[0098] S4-4: Methanol and ethanol are prepared into monomer solutions of different concentrations, the diaphragm adsorbed with the photoinitiator is placed in the monomer solution and filled with nitrogen for protection, the single-necked flask is placed in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, the diaphragm is continuously transported, and continuous irradiation grafting is performed. The surface properties of the battery diaphragm are improved by ultraviolet irradiation to induce surface grafting of polar monomers and increase its wettability to the electrolyte;
[0099] S4-5: After the irradiation is completed, the product is cleaned with distilled water, and after the cleaning is completed, vacuum drying is performed.
[0100] Example 3
[0101] A method for preparing a heat-resistant polymer semi-solid lithium battery separator comprises the following steps:
[0102] S1: Preparation of polyethylene diaphragm;
[0103] S2: Ceramic particle materials are selected to be coated on the surface of the polyethylene diaphragm. Ceramic particle materials have excellent mechanical properties, wear resistance and chemical stability. Polymer materials are used to improve the inherent defects of materials, give materials new functions and reduce the cost of material use;
[0104] S3: spray acrylic acid on the surface of the diaphragm to make it evenly adhere to the surface of the diaphragm;
[0105] S4: Use ultraviolet light irradiation to perform ultraviolet light grafting on acrylic acid and the separator to shape the surface material of the separator and perform surface grafting modification on the battery separator. As the grafting rate increases, the hydrophilicity of the separator increases, the air permeability increases, and the porosity and air permeability decrease;
[0106] S5: After drying, the separator is attached to the semi-solid lithium battery.
[0107] In this embodiment, in S1, the method for preparing the polyethylene diaphragm comprises the following steps:
[0108] S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet;
[0109] S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil;
[0110] S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller;
[0111] S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
[0112] In this embodiment, the method for preparing the ceramic particle material comprises the following steps:
[0113] S2-1: Add nano-alumina powder to special ceramic raw materials, and mix them separately. Nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials;
[0114] S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container;
[0115] S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas. The metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod to finally obtain ceramic nanoparticles. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of materials, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance;
[0116] S2-4: Introduce ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed. Ceramic nanoparticles have a large specific surface area and size effect, which can enhance the mechanical properties, thermal conductivity, and optical properties of the diaphragm surface, and can also improve the processing performance and density of the material.
[0117] In this embodiment, the acrylic acid in S3 is prepared by the following steps:
[0118] S3-1: After the hydrolysis temperature is set to 100°C, sulfuric acid with a concentration of 85% is added to acrylonitrile, and acrylonitrile is completely converted after 1 hour;
[0119] S3-2: The converted acrylonitrile is hydrolyzed for a second time by adding water, and the reaction temperature is increased to 125-135° C.;
[0120] S3-3: The hydrolyzate obtained after heating is decompressed, stabilized, and then distilled to obtain acrylic acid.
[0121] In this embodiment, the ultraviolet light grafting in S4 includes the following steps:
[0122] S4-1: After spraying acrylic acid on the cleaned surface of the diaphragm, dry it;
[0123] S4-2: dissolving the photoinitiator in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L;
[0124] S4-3: Soak the initiator solution on the surface of the diaphragm in the dark for 30 minutes;
[0125] S4-4: Methanol and ethanol are prepared into monomer solutions of different concentrations, the diaphragm adsorbed with the photoinitiator is placed in the monomer solution and filled with nitrogen for protection, the single-necked flask is placed in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, the diaphragm is continuously transported, and continuous irradiation grafting is performed. The surface properties of the battery diaphragm are improved by ultraviolet irradiation to induce surface grafting of polar monomers and increase its wettability to the electrolyte;
[0126] S4-5: After the irradiation is completed, the product is cleaned with distilled water, and after the cleaning is completed, vacuum drying is performed.
[0127] Comparative Example
[0128] A method for preparing a heat-resistant polymer semi-solid lithium battery separator comprises the following steps:
[0129] S1: Preparation of polyethylene diaphragm;
[0130] S2: Ceramic particle materials are selected to be coated on the surface of the polyethylene diaphragm. Ceramic particle materials have excellent mechanical properties, wear resistance and chemical stability. Polymer materials are used to improve the inherent defects of materials, give materials new functions and reduce the cost of material use;
[0131] S3: After drying, the diaphragm is attached to the semi-solid lithium battery.
[0132] In this embodiment, in S1, the method for preparing the polyethylene diaphragm comprises the following steps:
[0133] S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet;
[0134] S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil;
[0135] S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller;
[0136] S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
[0137] In this embodiment, the method for preparing the ceramic particle material comprises the following steps:
[0138] S2-1: Add nano-alumina powder to special ceramic raw materials, and mix them separately. Nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials;
[0139] S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container;
[0140] S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas. The metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod to finally obtain ceramic nanoparticles. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of materials, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance;
[0141] S2-4: Introduce ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed. Ceramic nanoparticles have a large specific surface area and size effect, which can enhance the mechanical properties, thermal conductivity, and optical properties of the diaphragm surface, and can also improve the processing performance and density of the material.
[0142] Compared with Example 1, the difference of the comparative example is that the semi-solid lithium battery separator is not sprayed with acrylic acid on the separator surface to make it evenly adhere to the separator surface, and the acrylic acid and the separator are not subjected to ultraviolet light grafting process by ultraviolet light irradiation.
[0143] It should be noted that the semi-solid lithium battery separators prepared in Examples 1-3 and the comparative examples were subjected to performance tests, wherein the performance test results of the semi-solid lithium battery separators are shown in Table 1:
[0144] Table 1: Performance test results of semi-solid lithium battery separator
[0145] Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example Acrylic acid hydrolysis temperature 90℃ 95℃ 100℃ none Sulfuric acid concentration 55% 70% 85% none Initiator concentration 0.43mol / L 0.43mol / L 0.43mol / L none Soaking time in dark 30min 30min 30min none Heat resistance temperature / ℃ 145 125 135 108 Heat shrinkage rate 100% 6.68% 7.05% 7.11% 8.15% Impact strength / g / mil 341 305 321 320
[0146] Therefore, it can be seen from the above table that the semi-solid lithium battery separator prepared according to the method for preparing the heat-resistant polymer semi-solid lithium battery separator provided in Examples 1-3 has high heat resistance and low thermal shrinkage, which can improve the overall safety and durability of the semi-solid lithium battery.
[0147] Working principle: The polyethylene material and the diluent are mixed and melted, solidified and formed into a rubber sheet. After the rubber sheet is dried and heated, it is immersed in the extractant for extraction to remove the internal oil. After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller. After forming, the film body is cut, wrapped and packaged for subsequent processing. Nano-alumina powder is added to the special ceramic raw materials, and the materials are divided, stirred and mixed. Nano-alumina powder has high hardness, high heat resistance and chemical stability, and can be used to prepare high-temperature ceramic materials. After mixing, the mixed powder is placed in a closed container and rotated, vibrated or violently shaken with the container. To obtain ultrafine particles, ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas, and the metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod to finally obtain ceramic nanoparticles. Ceramic nanoparticles can achieve microstructure regulation and performance optimization of materials, and have higher hardness, wear resistance, high temperature resistance, corrosion resistance and insulation performance. Ceramic nanoparticles are introduced into a sprayer, and the sprayer is moved at a constant speed to evenly spray on the surface of the diaphragm. Ceramic nanoparticles have a large specific surface area and size effect. The mechanical properties, thermal conductivity and optical properties of the membrane surface can be enhanced, and the processing properties and density of the material can also be improved. After the hydrolysis temperature is set to 90°C, sulfuric acid with a concentration of 55% is added to acrylonitrile. After 1 hour, the acrylonitrile is completely converted. The converted acrylonitrile is hydrolyzed for the second time by adding water, and the reaction temperature is increased to 125°C. The hydrolyzate obtained after heating is decompressed, and acrylic acid is obtained by distillation after stabilization. After the acrylic acid is sprayed on the surface of the cleaned membrane, it is dried, and the photoinitiator is dissolved in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L. , soak the initiator solution on the surface of the diaphragm and soak it in light for 30 minutes, prepare methanol and ethanol into monomer solutions of different concentrations, put the diaphragm adsorbed with photoinitiator into the monomer solution and fill it with nitrogen for protection, place the single-necked flask in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, continuously transport the diaphragm, and carry out continuous irradiation grafting. The method of ultraviolet irradiation inducing polar monomer surface grafting improves the surface properties of the battery diaphragm and increases its wettability to the electrolyte. After irradiation, it is washed with distilled water. After washing, it is vacuum dried. After drying, the diaphragm is attached to the semi-solid lithium battery.
[0148] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0149] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a heat-resistant polymer semi-solid lithium battery separator, characterized in that: The heat-resistant polymer semi-solid lithium battery separator is composed of a polyethylene separator, a ceramic particle material and acrylic acid. The preparation method of the heat-resistant polymer semi-solid lithium battery separator comprises the following steps: S1: Preparation of polyethylene diaphragm; S2: Select ceramic particle material and coat it on the surface of polyethylene diaphragm; S3: spray acrylic acid on the surface of the diaphragm to make it evenly adhere to the surface of the diaphragm; S4: UV light is used to perform UV grafting on acrylic acid and the diaphragm to shape the surface material of the diaphragm.
2. The method for preparing a heat-resistant polymer semi-solid lithium battery separator according to claim 1, characterized in that: In S1, the method for preparing a polyethylene diaphragm comprises the following steps: S1-1: Mixing and melting the polyethylene material and the diluent, and solidifying and forming the mixture into a rubber sheet; S1-2: After drying and heating the rubber sheet, immerse it in an extractant to perform extraction to remove the internal oil; S1-3: After the extraction, the rubber sheet is stretched and rolled into a film by a grinding roller; S1-4: After forming, the film is cut, wrapped and packaged for subsequent processing.
3. The method for preparing a heat-resistant polymer semi-solid lithium battery separator according to claim 1, characterized in that: The method for preparing the ceramic particle material comprises the following steps: S2-1: Adding nano-alumina powder to special ceramic raw materials, and mixing them; S2-2: After mixing, the mixed powder is placed in a closed container and ultrafine particles are obtained by rotating, vibrating or vigorously shaking the container; S2-3: Ultrafine particles are introduced into a vacuum evaporation chamber and filled with low-pressure inert gas, and the metal or compound evaporation source is heated. The resulting atomic mist collides with the inert gas atoms and loses energy, condenses into nano-sized clusters, and gathers on the liquid nitrogen cooling rod, finally obtaining ceramic nanoparticles; S2-4: Introduce the ceramic nanoparticles into the sprayer, and evenly spray them on the surface of the diaphragm by moving the sprayer at a constant speed.
4. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 1, characterized in that: The acrylic acid in S3 is prepared by the following steps: S3-1: After the hydrolysis temperature is set to 90-100°C, sulfuric acid with a concentration of 55%-85% is added to acrylonitrile, and acrylonitrile is completely converted after 1 hour; S3-2: The converted acrylonitrile is hydrolyzed for a second time by adding water, and the reaction temperature is increased to 125-135° C.; S3-3: The hydrolyzate obtained after heating is decompressed, stabilized, and then distilled to obtain acrylic acid.
5. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 4, characterized in that: The ultraviolet light grafting in S4 comprises the following steps: S4-1: After spraying acrylic acid on the cleaned surface of the diaphragm, dry it; S4-2: dissolving the photoinitiator in ethanol to prepare an initiator solution with a concentration of 0.43 mol / L; S4-3: Soak the initiator solution on the surface of the diaphragm in the dark for 30 minutes; S4-4: Methanol and ethanol are prepared into monomer solutions of different concentrations, the membrane adsorbed with the photoinitiator is placed in the monomer solution and filled with nitrogen for protection, the single-necked flask is placed in a constant temperature oven equipped with a 1000W ultraviolet lamp for irradiation, the membrane is continuously transported, and continuous irradiation grafting is performed; S4-5: After the irradiation is completed, the product is cleaned with distilled water, and after the cleaning is completed, vacuum drying is performed.
6. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 2, characterized in that: In S1-1, the polyethylene material is one of high-density polyethylene, low-pressure polyethylene, ultra-high molecular weight polyethylene, modified polyethylene, and cross-linked polyethylene.
7. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 2, characterized in that: In S1-2, the extractant is a neutral oxygen-containing extractant selected from alcohol ethers, ketones and ester compounds.
8. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 3, characterized in that: The raw material of the nano-alumina powder of S2-1 is obtained by dehydrating aluminum hydroxide at a low temperature of 140-150° C. to obtain type A alumina.
9. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 3, characterized in that: In S2-3, the low-pressure inert gas is one of helium, neon, argon, krypton and xenon with a gas pressure of 2 KPa.
10. The method for preparing a heat-resistant polymer-transformed semi-solid lithium battery separator according to claim 4, characterized in that: In S3-1, acrylonitrile is obtained by reacting acetylene and hydrocyanic acid at 80-90° C. under the catalysis of a dilute hydrochloric acid solution of cuprous chloride-potassium chloride-sodium chloride.
Citation Information
Patent Citations
A temperature-resistant and safe lithium-ion battery separator and its preparation method
CN103943804B